EFFECTS OF SOME RHIZOBACTERIA AND INDOLE-3-BUTYRIC ACID ON ROOTING OF BLACK AND WHITE MULBERRY HARDWOOD CUTTINGS - H. Zenginbal; T. Demir (Journal of Animal and Plant Sciences, 2018)
-1 This research was conducted to determine the effects of treatments with indole-3-butric acid ( 0, 2, 4 and 6 g l IBA) and plant growth promoting rhizobacteria (PGPR) ( Burkholderia gladii-BA7,Bacillussubtilus-OSU142 and Bacillusmegatorium-M3) strains have on rooting and root growth of hardwood stem cuttings of black and white mulberry both alone and in combination with each bacterial strain. Cuttings in the control group were treated with 50% ethanol + 50% distilled water. The hardwood stem cuttings (middle parts of one-year-old shoots) for rooting were selected from 15-year-old healthy donor black and white mulberries trees on February 1, 2015 and 2016 in Bolu, Turkey. The treated cuttings were placed in perlite medium in unheated trays of a greenhouse with automated misting system for 90 days. The rooting rate, root number, root length and diameter were evaluated. The rooting rate varied from 12.0 to 85.0%. The number of root varied from 2.05 to 10.19. The root length varied from 2.75 to 8.72 cm. The root diameter -1 varied from 0.81 to 2.49 mm. The results indicated that treatment with 4 g l IBA plus B. megatorium-M3 solution had a profound effect in increasing rooting capacity and quality in comparison to the control, and all other PGPR and IBA treatments. Overall, rooting rate and root quality of black mulberry hardwood cuttings was found to be lower than those -1 of white mulberry. Moreover, 4 g l IBA was the most appropriate dose and B. megatorium-M3 bacterial strain was the most appropriate rhizobacteria for rooting of mulberry cuttings. plants, collection time, environmental conditions and
Keywords: Mulberry; cutting; rooting; auxin; bacteria; propagation.